Comparison of the effectiveness of problem based learning (PBL) and project based learning (PjBL) models in the learning process - Herman Darmawan; Faisal Hakti; Rima Damayanti; Muhammad Fikri; Halim Rafi’i (Alifmatika (Jurnal pendidikan dan pembelajaran Matematika), 2024)
A learning model is a collection of methods, strategies, and the integration of methods used by teachers from start to finish. Choosing the right learning model can enhance the effectiveness and accuracy of the learning process. Additionally, learners can learn better due to the selection of the appropriate methods in the learning process, making the learning experience more engaging and ultimately impacting the quality of learning. This research aims to compare the PBL (Problem-Based Learning) and PjBL (Project-Based Learning) models and to determine the proper placement of these models in education. This study employs a qualitative-descriptive method with a semantic literature review. PBL is driven by problems faced by students and focuses on research and investigation, whereas the PjBL approach is driven by the final product they aim to produce, with the primary focus on the entire production process. PBL begins with a problem, and that problem becomes the main focus in PBL, where every progress, plan, and effort made by students is directed towards solving the problem. On the other hand, PjBL starts with the assignment to carry out one or more tasks leading to the production of a final product.